2020
DOI: 10.15252/embj.2019104324
|View full text |Cite
|
Sign up to set email alerts
|

Transient exposure to miR‐203 enhances the differentiation capacity of established pluripotent stem cells

Abstract: Full differentiation potential along with self‐renewal capacity is a major property of pluripotent stem cells (PSCs). However, the differentiation capacity frequently decreases during expansion of PSCs in vitro. We show here that transient exposure to a single microRNA, expressed at early stages during normal development, improves the differentiation capacity of already‐established murine and human PSCs. Short exposure to miR‐203 in PSCs (miPSCs) induces a transient expression of 2C markers that later results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 66 publications
3
21
0
Order By: Relevance
“…There are 43 exosomal miRNAs highly expressed in MC3T3-E1 cells during the osteogenesis process, such as miR-30d-5p and miR-133b-3p [ 44 , 45 ]. Moreover, miR-135b , miR-203 , and miR-299-5p are upregulated in human-BMSCs derived exosomes during osteogenesis [ 46 48 ]. Thus, in the present study, we aimed to identify the differences in exosomal miRNAs between N-Exos and DM-Exos.…”
Section: Discussionmentioning
confidence: 99%
“…There are 43 exosomal miRNAs highly expressed in MC3T3-E1 cells during the osteogenesis process, such as miR-30d-5p and miR-133b-3p [ 44 , 45 ]. Moreover, miR-135b , miR-203 , and miR-299-5p are upregulated in human-BMSCs derived exosomes during osteogenesis [ 46 48 ]. Thus, in the present study, we aimed to identify the differences in exosomal miRNAs between N-Exos and DM-Exos.…”
Section: Discussionmentioning
confidence: 99%
“…There are 43 exosomal miRNAs highly expressed in MC3T3-E1 cells during the osteogenesis process, such as miR-30d-5p and miR-133b-3p (Li et al, 2008;Zhang et al, 2011). Moreover, miR-135b, miR-203, and miR-299-5p are upregulated in human-BMSCs derived exosomes during osteogenesis (Panganiban et al, 2016;Salazar-Roa et al, 2020;Schaap-Oziemlak et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to miR-1 and miR-499, overexpression of miR-203 improves efficient differentiation and maturation to cardiomyocytes by repression of DNA methyltransferase 3a/b (Dnmt3a/b) in mouse iPSCs ( Salazar-Roa et al, 2020 ). miR-322 and miR-503 clusters have shown that participate in the specification into cardiomyocyte progenitors of the mesodermal cells by the repression of CUGBP Elav-like family member (Celf) family proteins ( Shen et al, 2016 ).…”
Section: Part 2: Mirnas and Cardiac Regenerationmentioning
confidence: 99%